Atorvastatin as an immunomodulatory adjunct in ulcerative colitis, beyond lipid lowering to inflammation control: a randomized controlled pilot study - Khrieba, Mohannad O.; Abdulelah, Furqan M.; Alsaleh, Nada A.; AlRasheed, Hayam Ali; Ahmed, Tarek I.; El-Sayed Mansy, Azza; Hamouda, Manal A.; Habba, Eslam; Elshorbagi, Nora; Abd Elhameed, Ahmed G.; Hamza, Eman; Salahuddin, Muhammed M.; et al. (Frontiers in Pharmacology, 2025)
BackgroundUlcerative colitis (UC) is a long-term condition marked by recurrent episodes of inflammation affecting the colonic mucosa. Despite mesalamine’s or 5-amino salicylic acid’s (5-ASA) established role in inducing and maintaining remission, some patients experience persistent symptoms and inflammatory activity. Atorvastatin has pleiotropic anti-inflammatory effects, and provide therapeutic benefits in UC. Several preclinical studies assessed the beneficial role of atorvastatin in colitis, but clinical data remain scarce.AimTo evaluate the efficacy and safety of 5-ASA plus atorvastatin (versus 5-ASA plus placebo) in patients with mild to moderate UC.MethodsIn this randomized, double-blind Pilot trial, 54 patients with mild-to-moderate UC were randomized to receive 5-ASA plus atorvastatin (Atorvastatin group, n = 27) or 5-ASA plus placebo (Control group, n = 27) for 6 months. Clinical activity was assessed using the Simple Clinical Colitis Activity Index (SCCAI), quality of life using the Inflammatory Bowel Disease Questionnaire (IBDQ-32), and inflammatory status using serum interleukin-18 (IL-18), C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR). Statistical analysis was conducted using intention to treat.ResultsAfter treatment, both groups showed significant changes in all measured parameters when compared to baseline except for bowel frequency at night in control group (p = 0.148). When compared to the control group, the atorvastatin group demonstrated significantly greater post-treatment improvements in IBDQ systemic (p = 0.001), digestive (p = 0.013), emotional domains (p = 0.015), and total score (p = 0.003). Reductions in IL-18, CRP, and ESR were observed in both groups, but were significantly greater with atorvastatin (IL-18: p = 0.026; CRP: p = 0.027; ESR: p = 0.03, SCCAI: p = 0.0005). Clinical response was achieved in 66.6% of atorvastatin-treated patients versus 44% of controls (p = 0.02). Spearman’s analysis showed IBDQ-32 scores were negatively correlated with SCCAI (r = −0.498), ESR (r = −0.549), CRP (r = −0.356), and IL-18 (r = −0.548). No significant reported side effects.ConclusionAdjunctive atorvastatin with 5-ASA significantly improved clinical disease activity, quality of life, and inflammatory biomarkers compared to 5-ASA alone in mild-to-moderate patients with UC.Clinical Trial Registrationclinicaltrials.gov, Identifier NCT05567068.